A House is a Figure between the Earth and the Sky Case Study: Batak Toba House in Samosir Island - Himasari Hanan (RUAS (Review of Urbanism and Architectural Studies), 2011)
Vernacular architecture is not simply determined externally by the natural forces of its physical context. The poetic expression of Batak Toba house must have involved creative imagination in the mind of the people that may reflect the structure of mental models that constitute the thinking. This paper is intended to explore the presence of “generative concepts” of building’s form and its architecture, which is based on the figuration of relationship between man and the nature. Three Batak Toba settlements in Samosir island are selected for the analysis of the archetypes in Batak architecture in the attempt to understand the existential basis of architecture.Keywords: archetype, anthropomorphic, house on stilts, Batak Toba